The Impact of Companies not Implementing Corporate Social Responsibility on Financial Performace : Literature Review - Salsabila Alya Maharany; Sofinatus Solikhah; Hwihanus Hwihanus (Fakultas Ekonomi Program Studi Akuntansi Universitas 45 Surabaya, 2024)
This research was conducted to determine the impact of the influence of Corporate Social Responsibility (CSR) on financial performance in several countries. This research was conducted with the aim of comparing the results of research on the influence of corporate social responsibility on financial performance in various countries and industries. The method used in this research is meta-analysis using qualitative methods in the form of international journals from several countries including India, China, Thailand, United States Kingdom. The results showed that CSR does not always provide consistent results. This study concludes that although Corporate Social Responsibility (CSR) on financial performance has a positive correlation, it is still considered trivial by companies in various countries.